10h-8h+h-3h+h=7

Simple and best practice solution for 10h-8h+h-3h+h=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10h-8h+h-3h+h=7 equation:


Simplifying
10h + -8h + h + -3h + h = 7

Combine like terms: 10h + -8h = 2h
2h + h + -3h + h = 7

Combine like terms: 2h + h = 3h
3h + -3h + h = 7

Combine like terms: 3h + -3h = 0
0 + h = 7
h = 7

Solving
h = 7

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Simplifying
h = 7

See similar equations:

| 5+3(x+4)=-(2x-1)-9 | | log[4](13*7)= | | 5r^2-10r-15=0 | | 2x^3+13x=8x^2 | | -17-55p=5(2+4p)+2p | | 20-2=38 | | -3(x-4)+2xy=xy-5x+xy-6 | | 2w^2-22w+48=0 | | 5(2)-2=38 | | (3g+2)(9g+5)=0 | | 5(10)-2=38 | | 300+12=960 | | 6-(x+9)=3-4x | | 10x-7y=-42 | | (d-6)(d-2)=0 | | 3(8)+7=25 | | 8(x+1)+3=7x+18 | | 3x-5(x+2)=12x+4 | | (v-7)(v-6)=0 | | 0.27t=129 | | 3+x=43 | | 96c^2+336c+294=0 | | 2(3)-5=17 | | v^2=-14+9v | | 5y-3=10y+4 | | 4k(3k+4)=0 | | 96c+336+284=0 | | =9(-6-x)-8x | | x^4+x^2-720=0 | | 15(t-6)+3t=6(3t+3)-12 | | 45x-5y=6.6 | | 3x^2-16+16=0 |

Equations solver categories